PENYULUHAN PENINGKATKAN KUALITAS PRODUK PADA PENGRAJIN USAHA MIKRO SUKASARI DESA BADERAN KECAMATAN GENENG KABUPATEN NGAWI - Endang Murti; Isni Wahidiyah Susanto; Retno Iswati; DS Martono (Universitas Merdeka Madiun, 2022)
The Small and Medium Enterprises (UKM) sector is an industry that competes to advance the economy in Indonesia. One of the business fields that can develop and be consistent in the national economy, UKM must have a competitive strategy, including the advantages of high product quality and competitive prices. For example, one of the superior products of Baderan village is Suka Sari. Suka Sari is a brand of processed traditional herbal medicine in the form of powder which is the main product of Baderan Village. Suka Sari is produced by a home industry in Mlarik Hamlet RT.01 RW.01 Geneng District, Ngawi Regency. This research uses the methods of counseling, training, mentoring, use of technology, and partner participation. After the implementation of this community service, it can be concluded that the results of the activities are as follows: Partners' understanding of the need for good and healthy business management and empowerment must be improved. Professional business management training is needed to develop their business.There is assistance in the production process and marketing of products so that they can compete with competitors' products and Introduce appropriate technology (use of the internet for product marketing).